Relationship between age, occupation, education, and parity with the chronic energy deficiency among pregnant women - Auranissa, Aliefia; Zuhairini, Yenni; Nurdiawan, Windi (Intelektual Pustaka Media Utama, 2024)
Maternal and child health quality depends on maternal nutrition during pregnancy. Chronic energy deficiency (CED), a malnutrition condition common in pregnant women, increases the risk of the mother experiencing postpartum hemorrhage and the fetus experiencing intrauterine growth restriction (IUGR). The prevalence of CED risk among pregnant women in Sukabumi City, West Java, Indonesia is unstable and has not significantly decreased. This study aimed to determine the relationship between age, occupation, education, and parity with the risk of CED among pregnant women in Sukabumi City. An analytical observational study with a case-control approach using cluster sampling was conducted on 126 pregnant women with and without CED risk, respectively. The population for this study was pregnant women who checked at the primary health center in Sukabumi City in 2021. Data were collected from maternity health record and analyzed using Chi-square. The results showed that age had a significant relationship (p=0.000). In contrast, occupation (p=0.162), education (p=0.127), and parity (p=0.313) did not have a significant relationship with the risk of CED among pregnant women in Sukabumi City. Age was associated with the risk of CED among pregnant women in Sukabumi City.